Faktor Pendukung Penanaman Moral Anak Usia Dini DI Taman Kanak-kanak - Zulilana, Endang (GHAITSA : Islamic Education Journal, 2021)
Morals are a way of understanding what is right or wrong, namely having good ethics and acting appropriately. Morals are very important to support future social life, such as not acting evilly, understanding what other people are suffering, listening before judging others, respecting differences, being empathetic, showing love and respect for parents, family and other people. The aim of the research is to determine the supporting factors for instilling morals in early childhood at TKIT Ummi Bengkulu. The research method uses descriptive qualitative which includes interviews, observation and documentation. The subjects interviewed were teachers and students of TKIT Ummi Bengkulu. Teachers will teach children to have good behavior, say hello and kiss the hands of parents and teachers when leaving and going to school. Apart from that, teachers at school become role models for students at school in terms of how to dress, speak and behave. So that children will become polite individuals towards friends and teachers, children will have an honest attitude, respect friends and teachers during teaching